A Literature Review on Culture-Based Digital Storytelling to Enhance EFL Students’ English Writing Skills - Arifah, Tanalina; Wijayatiningsih, Testiana Deni; Setiawan, Anjar (Journal of English Education and Linguistics, 2025)
This study explores the potential of culture-based digital storytelling as a pedagogical approach to enhancing English writing skills among learners of English as a Foreign Language (EFL) by integrating multimodal learning features with culturally familiar narratives. Adopting a literature review methodology, the study synthesizes findings from 27 peer-reviewed journal articles published between 2010 and 2024 that examine EFL writing challenges, instructional strategies, digital storytelling practices, and the incorporation of cultural materials in language learning. The synthesis reveals that EFL learners frequently encounter difficulties in idea generation, textual coherence, and linguistic accuracy, challenges that are often exacerbated by cognitive overload and affective barriers. The reviewed studies indicate that digital storytelling supports writing development by providing multimodal scaffolding through the integration of visual, auditory, and textual modes, which enhances learners’ comprehension, engagement, and narrative organization. In addition, the use of culturally familiar narratives, particularly local folklore, facilitates conceptual understanding, reduces cognitive demands, and fosters emotional connection with writing tasks. The findings suggest that culture-based digital storytelling constitutes a mutually reinforcing instructional model in which multimodal support and cultural relevance jointly address both cognitive and affective dimensions of writing. This integrated approach enables learners to construct and express ideas more meaningfully in written form. The study concludes that culture-based digital storytelling offers a pedagogically sound framework for strengthening EFL learners’ narrative writing competence and emphasizes the need for further empirical research to investigate its classroom implementation and effectiveness across diverse educational contexts.